Gambaran Maloklusi Relaps Pada Pasien Ortodonti Usia Dewasa Di RSGM-P Usakti - Berliana, Dinda; Zen, Yuniar (Jurnal Kedokteran Gigi Terpadu, 2025)
Background: Orthodontic treatment relapse is a condition where previously treated teeth in orthodontic treatment undergo malocclusion again, forming a new malocclusion. Someone who has had orthodontic treatment that results in relapse or forming a new malocclusion requiring re-orthodontic treatment. Relapse Post-orthodontic treatment can arise from several factors, including short-term retention, incomplete treatment, inappropriate retention devices, and bad habits of the patient. Objective: The aim of this study is to determine the description of malocclusion due to relapse in adult orthodontic patients at RSGM-P FKG Universitas Trisakti Methods: This research was conducted using a descriptive observational method using a research design cross-sectional. The sample in this study was 21 patients with medical records relapse post-orthodontic treatment who came to RSGM-P FKG Universitas Trisakti. The data collected from the patient's medical records, using consecutive sampling method will be analyzed to identify features of the resulting malocclusion relapse in patients at RSGM-P FKG Universitas Trisakti the measurement scale is the nominal scale. Results: The molar relationship of relapsed patients who came to the academic clinic of RSGM-P FKG Universitas Trisakti for the period 2020-2022 was mostly class I malocclusion. The malocclusion status of relapsed patients who came to the academic clinic of RSGM-P FKG Universitas Trisakti for the period 2020-2022 was crowding. The malocclusion description of relapsed patients who came to the academic clinic of RSGM-P FKG Universitas Trisakti for the period 2020-2022 was mostly class I type 1 malocclusion (62%). Conclusion: The malocclusion description of adult relapsed patient who come to the academic orthodontic clinic RSGM-P FKG Universitas Trisakti is malocclusion class I type 1 in 12 cases, malocclusion class I type 2 in 1 case, malocclusion class I type 3 in 1 case, malocclusion class II division 1 in 3 cases, malocclusion class II division 2 in 1 case, malocclusion class I type 1 and 2 in 1 case, malocclusion class I type 1 with deep bite in 1 case, malocclusion class II division 1 with crowding in 1 case.